ANALISIS BIBLIOMETRIK TOPIK PENELITIAN PEREMPUAN POLITIK DI INDONESIA MENGGUNAKAN VOSVIEWER - Pujiastuti, Ana (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The increasing number of women who enter the world of politics in Indonesia is the background for the development of publications that review this matter. This phenomenon inspires other women to be confident in actualizing themselves in public. The purpose of this study is to determine the development of research topics per year and a map of research on political women in Indonesia. The research methodology used in this research is bibliometric analysis with VOSviewer. Data is taken from Harzing's Publish or Perish for 2019–2021. The results of this study indicate that the development of research on the topic of political women in Indonesia has decreased every year, one of the factors being triggered by limited activities outside the home during the pandemic. Meanwhile, the research map on the topic of political women in Indonesia in the last three years gives a sign of the development of a democratic climate in Indonesia. This is indicated by the active participation of women in the political sphere. Women have the opportunity to express their opinions, fight for the aspirations of their constituents, and have the same rights to maintain the stability of democracy in Indonesia.Meningkatnya jumlah perempuan yang terjun ke dunia politik di Indonesia melatarbelakangi berkembangnya publikasi yang mengulas mengenai hal tersebut. Fenomena ini menjadikan inspirasi bagi perempuan yang lain untuk percaya diri mengaktualisasikan diri di hadapan umum. Tujuan penelitian ini untuk mengetahui perkembangan topik penelitian per tahun dan peta penelitian mengenai perempuan politik di Indonesia. Metodologi penelitian yang digunakan dalam penelitian yakni analisis bibliometrik dengan VOSviewer. Data diambil dari Publish or Perish selama tahun 2019-2021. Hasil dari penelitian ini menunjukkan perkembangan penelitian mengenai topik perempuan politik di Indonesia mengalami penurunan di setiap tahunnya yang salah satu faktornya dipicu terbatasnya aktivitas di luar rumah selama pandemi. Sedangkan peta penelitian dengan topik perempuan politik di Indonesia tiga tahun terakhir memberikan tanda berkembangnya iklim demokrasi di Indonesia. Hal ini ditandai dengan partisipasi aktif para perempuan di ranah politik. Para perempuan berkesempatan untuk mengeluarkan pendapat, memperjuangkan aspirasi konstituen, dan mempunyai hak yang sama untuk menjaga kestabilan demokrasi di Tanah Air Indonesia.